AN ETNOLINGUISTICS STUDY: DEVELOPING AWARENESS AND RESPONSES OF LOCAL WISDOM IN TEACHING ENGLISH - U Komara; Ratu Sarah Pujasari (Asosiasi dosen IDEBAHASA KEPRI, 2019)
As the students coming to senior high schools becomes more diverse, English teachers will bear a larger responsibility to perform a better teaching with different cultural backgrounds. This research illustrates how ethnographic studies with awareness and responses of local wisdom are implemented and performed by the English teachers during teaching and learning process in the classroom. The research investigates how teachers perform their awareness and responses of local wisdom in their teaching English with three specific purposes: 1) to explore how the teachers perform communicative language teaching with their awareness and responses of local cultures; 2) to explore the objects of awareness in their teaching services that could help the learners develop their communicative competence; and 3) to explore the ways the teachers respond to the learners during the teaching-learning process. The researcher uses a descriptive qualitative method that aims at exploring and describing the current issues that may probably occur while conducting the research. To gain the data, the researcher uses observation and semi-structured interview.